Talent management in the manufacturing sector: A systemic literature review - Nurul Ezaili Alias; Norashikin Hussein; Koe Wei-Loon; Najihah Hanisah Marmaya (ResearchGate, 2023)
This article conducts a systematic literature review (SLR) analysis and relates to talent management (TM) in the manufacturing industry. The objectives are first, to provide a comprehensive analysis of TM research in the manufacturing industry; second, to identify and discuss key research topics, and third, to recommend avenues for future research. The study examines publications that were published between 2008 and 2022, which were thoroughly searched and obtained from four established databases: Scopus, Web of Science, Mendeley, and Google Scholar. According to the findings, academics are becoming more interested in TM in the manufacturing industry, which appears to be related to a scarcity of talent with high knowledge, skills, and abilities (KSAs), which contributes to negative organisational outcomes. The article presents findings that have relevance for both academia and practitioners. It provides data on existing research while also emphasizing the need for further investigation into the discovery, value, and implementation of TM. As a result, this article offers a pathway for researchers to conduct empirical studies on the role of TM practices in effectively and efficiently managing manufacturing talent with high KSAs. Furthermore, the article adheres to the preferred reporting items for systematic reviews and meta-analysis (PRISMA) requirements for SLRs, ensuring a structured approach to the content and methodology of the study.